Diffusion of Brazil’s public procurement policies in Latin America and the Caribbean - Caldas, Eduardo de Lima (2018)
This article analyzes the influence of Brazilian ideas on changes in buy public in both countries: Haiti and Paraguay. Theoretically, it is proposed a discussion about diffusion, circulation and transfer of ideas and public policies. As results, a hybrid construction was observed in both countries. Thus, even though Brazilian ideas, instruments and learning have been diffused and transferred to those countries, institutional formats have been translated into their respective national contexts. Public policies of public buy in Haiti and Paraguay are closer to 'translations' than pure transference, considering that the translation of public policy involves several processes like mutations, interpretations, 'bricolage' and trial and error.